2021
DOI: 10.17398/2340-2784.41.83
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges between audiovisual translation and English for Specific Purposes

Abstract: Audiovisual translation (AVT) has been exhaustively studied from various perspectives such as Cross-cultural Studies or Reception Studies. More recently, attention has been paid to its value in teaching foreign languages. However, in spite of the numerous descriptive papers on the didactic potential of AVT, relatively few are based on empirical research and even fewer when referring to the teaching of English for Specific Purposes (ESP). Thus, this case study aims to contribute to this field by taking the puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…Por su parte, el GE parte de una media más baja en el test inicial (4,182), pero experimenta una mejora más marcada, de 2,811 puntos, y obtiene una media en el test final de 6,993. Por ello, a pesar de que los resultados en el GE fueron inferiores, pudiendo estar justificados por el tipo de audio utilizado, más próximo a un discurso oral real que el de una pista de audio graduada como la del GC, parece que el uso de materiales reales pueda contribuir a una mayor mejora a largo plazo, corroborando los beneficios del uso didáctico de los subtítulos para el desarrollo de la destreza de recepción oral planteados en estudios previos (Fuentes-Luque y Campbell, 2020; Gonzalez-Vera, 2021).…”
Section: Evolución De Los Resultados Del Gc Con Los Del Ge En Las Des...unclassified
See 2 more Smart Citations
“…Por su parte, el GE parte de una media más baja en el test inicial (4,182), pero experimenta una mejora más marcada, de 2,811 puntos, y obtiene una media en el test final de 6,993. Por ello, a pesar de que los resultados en el GE fueron inferiores, pudiendo estar justificados por el tipo de audio utilizado, más próximo a un discurso oral real que el de una pista de audio graduada como la del GC, parece que el uso de materiales reales pueda contribuir a una mayor mejora a largo plazo, corroborando los beneficios del uso didáctico de los subtítulos para el desarrollo de la destreza de recepción oral planteados en estudios previos (Fuentes-Luque y Campbell, 2020; Gonzalez-Vera, 2021).…”
Section: Evolución De Los Resultados Del Gc Con Los Del Ge En Las Des...unclassified
“…Los resultados obtenidos en este estudio confirman los de investigaciones previas, como las ya mencionadas de Talaván (2006;, Fuentes-Luque y Campbell (2020), Ávila-Cabrera (2021), Ávila-Cabrera y Corral Esteban, (2021), Ávila-Cabrera y Rodríguez-Arancón (2021) y Gonzalez-Vera (2021), donde se constata un efecto positivo en el uso didáctico de los subtítulos en el proceso de aprendizaje de lenguas extranjeras. Hay que señalar, no obstante, que este estudio se limitaba a una unidad didáctica y al uso de una modalidad de TAV, la subtitulación.…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…In particular, the participants realized that the existing provided teaching materials have not met their language learning needs because of classroom regulations to use English, inadequate English for education, and global teaching contents. More recently, the scrutiny concentrated on the contributions of audiovisual translation (AVT) to teaching listening comprehension in the ESP context [28]. He concluded that AVT enabled students to enhance their listening skills (e.g., listening comprehension) through the deployment of authentic teaching materials.…”
Section: Introductionmentioning
confidence: 99%